Redescriptions of three species of Pulvinaria (Hemiptera: Coccomorpha: Coccidae) in Japan - Tanaka, Hirotaka (Zootaxa, 2020)
Three Japanese species of the genus Pulvinaria Targioni Tozzetti (P. araliae Shinji, 1935, P. enkianthi Takahashi, 1955 and P. flava Takahashi, 1955) are redescribed and illustrated based on type specimens and some newly collected adult female specimens. Lectotypes are designated for P. enkianthi and P. flava from syntypes of these species and, in the absence of any original material, a neotype is designated for P. araliae using a specimen collected from the type locality. To facilitate comparisons, a table of diagnostic morphological character states of the redescribed species and the type species of the genus, P. vitis (Linnaeus, 1758), is also provided.